Foreign Body Granuloma in the Tongue by a Pequi Spine - Rafael Martins Afonso Pereira; Patrícia Cristine de Oliveira Afonso Pereira; Vitor Carvalho Rodrigues; Luiz Fernando Braga de Andrade; Elisa Morais de Carvalho; Helvécio Marangon Júnior (Hindawi Limited, 2020)
Substances considered foreign to the human organism can penetrate it due to local trauma, initially causing an acute inflammatory response against these substances, involving a neutrophilic infiltrate that, when it fails to deal with these foreign bodies, ends up generating a granulomatous inflammatory response. Granuloma formation has been associated with a variety of conditions. The correct clinical and imaging diagnoses are extremely important for the dentist to choose an appropriate therapeutic approach, aiming at the best possible treatment. This work is aimed at describing a case report of a foreign body granuloma, formed on the tongue, from the penetration of a pequi spine, in a 76-year-old patient, in whom, after an imaging diagnosis with ultrasound, surgical removal of the lesion was performed, and the piece was sent for histopathological examination, which confirmed the initial diagnostic hypothesis of a foreign body granuloma. The initial diagnosis of foreign body granulomas is challenging. For this reason, more sophisticated means of diagnosis such as tomography and magnetic resonance become important in the diagnosis, as they can show with greater clarity and reliability the nature of the lesion and its relationship with adjacent anatomical structures. In the case in question, an ultrasound examination was chosen, which was extremely important as an aid to diagnosis, considerably improving surgical planning. In addition, after surgical removal, the result of the histopathological analysis is essential to determine the definitive diagnosis, as it determines the granulomatous characteristic of the lesion.